2021
DOI: 10.1002/advs.202100805
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Fiber‐Hydrogel Based Non‐Viral Gene Delivery Platform Reveals that microRNAs Promote Axon Regeneration and Enhance Functional Recovery Following Spinal Cord Injury

Abstract: Current treatment approaches toward spinal cord injuries (SCI) have mainly focused on overcoming the inhibitory microenvironment that surrounds lesion sites. Unfortunately, the mere modulation of the cell/tissue microenvironment is often insufficient to achieve desired functional recovery. Therefore, stimulating the intrinsic growth ability of injured neurons becomes crucial. MicroRNAs (miRs) play significant roles during axon regeneration by regulating local protein synthesis at growth cones. However, one cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 87 publications
(150 reference statements)
0
41
1
Order By: Relevance
“…Some scholars also combine collagen with neurotrophic factor 3 (NT-3)/brain-derived nerve growth factor (BDNF) through the collagen binding domain and use the slow-release characteristics of recombinant collagen and the biological properties of growth factors to construct bioactive scaffolds [ 208 , 209 ]. Zhang et al used hydrogel scaffolds encapsulated with a variety of microRNAs and neurotrophic factors for animal model research, by regulating the expression of proinflammatory genes and extracellular matrix deposition-related genes and promoting local protein synthesis in growth cones that play an important role in axonal growth and development to improve nerve damage [ 210 ]. Histological, behavioral, and electrophysiological analysis showed that the above bioactive scaffolds could effectively promote the growth of axons and ultimately promote tissue repair.…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…Some scholars also combine collagen with neurotrophic factor 3 (NT-3)/brain-derived nerve growth factor (BDNF) through the collagen binding domain and use the slow-release characteristics of recombinant collagen and the biological properties of growth factors to construct bioactive scaffolds [ 208 , 209 ]. Zhang et al used hydrogel scaffolds encapsulated with a variety of microRNAs and neurotrophic factors for animal model research, by regulating the expression of proinflammatory genes and extracellular matrix deposition-related genes and promoting local protein synthesis in growth cones that play an important role in axonal growth and development to improve nerve damage [ 210 ]. Histological, behavioral, and electrophysiological analysis showed that the above bioactive scaffolds could effectively promote the growth of axons and ultimately promote tissue repair.…”
Section: Treatment Strategies For Scimentioning
confidence: 99%
“…Although several advanced techniques have been developed to generate 3D electrospun scaffolds capable of enhancing cellular infiltration, they still have a few limitations that could be improved for NTE application 23 . First, most of the previous 3D electrospun scaffolds were composed of randomly oriented nanofibres and uncontrolled porosity, which are not suitable for highly organized neural tissues 12,24 . Although a few post-processing technologies, such as ultrasonication, might preserve the oriented topographic cues, the molecular weights of materials and mechanical properties of nanofibres would be significantly affected by insufficient thickness and uneven geometry 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Beside glial scar formation, enhancement was noted in the release of neurotrophic factors that provide a favorable microenvironment to enhance axonal regeneration and to improve the locomotor recovery in rats after 8 weeks of scaffolds post-transplantation. An important contribution in the advancement of spinal cord (SC) and CNS regeneration is the work performed by Chew and co-workers [153][154][155], who managed to promote OPC differentiation, axon regeneration and CNS remyelination in vivo through a hybrid scaffolding system consisting of core bundle aligned PCLEEP fibers structurally stabilized in a 3D conformation using collagen hydrogel encapsulating different cocktail of miRNAs, which were capable of assuring the localized and sustained delivery of promyelinogenic biomolecules within the injured CNS as well as of enhancing axion regeneration in SC injuries. Based on a complex in vivo investigation, the authors demonstrated that the proposed fiber-hydrogel scaffold can enhance the number of Olig 2+ oligodendroglial lineage cells, differentiate OLs and remyelination and significantly promote functional recovery after post-treatment in rats.…”
Section: Recent Advances Of Electrospun Fibrous Architectures As Amen...mentioning
confidence: 99%